A health's view on violence - Paula Borges Jacques; Querubina Bringel Olinda (Universidade de Fortaleza, 2012)
Violence is the intentional use of physical strength or power, actually or under threat, against oneself, someone else, or against a group or community, which results or has a high probability of resulting in injury, death or psychological damage, bad development or deprivation(1).In Brazil and in the world, a lot is told about violence, which is present in various forms in everyday life, whether in the country or in urban area. Cities have grown without proper planning, people have migrated, generating unsatisfied social demands in the large centers, television has invaded home and modified people's thinking in great extension, families have loosen moral principles, governments do not set good examples...Therefore, violence has spread into all aspects of life, revealing itself in economics (exploitation of man by man, state coercion, material dependence, discrimination against women's work, child labour, unfair impositions etc.), in politics (control by one or various parties, authoritarianism, exclusion of citizens from decision-making, revolution, war and armed conflict etc.), in ideology (implementation of official criteria, prohibition of free thought, censorship, manipulation of public opinion, advertisements and issues of violent nature), in religion (submission to clerical interests, strict control of thought, prohibition of other beliefs and persecution of "heretics", etc.), within the family (exploitation of women and children etc..), in education (teachers and principals authoritarianism etc.), in the army (unquestioning obedience to commanders etc.), in the culture (excluding innovating trends, prohibiting publication of works, bureaucracies, etc.)... (2)It is health's responsibility dealing with people affected by physical or psychological violence, in hospitals, ambulatory facilities or clinics... As researches in health are responsible for statistical data consolidation. In 2002, the World Health Organization (WHO) released its first report on violence and health, achieving a comprehensive review on the matter of violence (what it is, whom it affects and how to deal with it), bringing a closer look at the issue, which haunts governments of all countries(3). Since then, violence has advanced through the governmental and social sphere, onto its intersection with health, either in the resultant presented by mortality and morbidity indicators, or in the costs given rise by the public network of medical psychological and hospital support to the victims of violence, and also in the contribution for preventive strategies.The fact is that society has been losing its benchmark, while receiving an avalanche of information, not always filtered. Crime has become as commonplace in the fiction of soap operas as in people's lives. Kindness in relationships and in attitudes is being lost. Slightly repeated rudeness become unbearable for those who are daily affected.The habit makes the addiction, physical violence strikes, which is a cowardice, because it always sets the strongest against the weakest, man against woman, the mighty against the humble, adult against child, characterizing interpersonal acts of violence(4), classified into two spheres: within the families and the community. Violence within the families is the one that takes place among intimate partners and relatives, mainly at household environment, but not solely. It includes different kinds of aggression against children, against man and woman and against the elderly(4).Many forms and levels of violence extend up to the most serious points - physical disability and homicide. Community violence(4) is defined as the one that occurs in general social environment, among acquaintances and strangers, represented by youth violence, physical aggression, rapes, sexual mistreatment and, also, institutional violence, which occurs in schools, working environments, prisons and shelters(4).However, violence means a void of the State and, as the law of matter rules, when a space is empty, something else occupies it - in this particular case, the criminal organizations. Collective violence arises(4), with violent acts that occur in macro-social, political and economic fields, and characterize the domination by groups and the State. In this category (4), from the social point of view, are included crimes committed by organized groups, crowns and acts of terrorism. In the political field, there are wars andannihilation processes perpetrated against certain people and nations by others(4). In addition to the classification established by the WHO Report (2002), there is another type of violence, called structural violence(4), referring to social, political and economic processes, which are responsible for reproducing hunger, poverty and inequality in social, gender and ethnics aspects, also rendering them chronic and maintaining the adult-centered dominance over children and adolescents. Hardly quantified and apparently without actors, the structural violence perpetuates itself into historical processes, becomes persistent and natural in the culture, taking in its account privileges and forms of domination. Most types of violence previously cited are based on the structural violence (4).Nowadays, one lives in fear and, being afraid, one does not live. Life is for the strong, for those who believe in it and react to adversities. Citizen is afraid to take a stroll in the streets; to flaunt a jewel; to drive a vehicle more powerful than usual, in order not to attract attention. Families fear for their children on the internet because of pedophiles and are afraid of the drug that has spread not only into the capital cities, but also into the countryside. The Brazilian State has neglected its boundaries, drug has come inside and got established, making victims each day and letting families unsettled, frightened, in pain, with nowhere to go. A public policy is needed to protect the youth, to recover theaddicts and safeguard our borders. How many young people have had their careers interrupted! How many abandoned children are in the hands of criminals committing crime?The damages, injuries, traumas and deaths caused by accidents and violence correspond to high emotional and social costs, and to expenses related to public safety apparatuses. They give rise to financial losses caused by absence to work, by incommensurable mental and emotional damage provoked in the victims and their families, and by wasted years of productivity and life. Into the health system, the consequences of violence, among other aspects, become evidenced by the increasing expenses of emergency, care and rehabilitation services, much higher than costs of regular medical proceedings(5).Research is fundamental to the development of programs and policies on violence prevention. It is crucial that the health sector involves the scientific community, including universities, research institutes, and science councils. To achieve success, a public health approach to violence prevention should be conducted and coordinated by a "leading agency" that could set the agenda for the prevention and strengthen the roles played by other partners(6).In order to collaborate to the prevention of violence, Brazilian Journal in Health Promotion presents relevant articles over the years, drawing the attention of students, professionals and health managers to such a strong and full of data issue, that grieves everyone. Because peace is everyone's responsibility, a citizen's right and a duty of the State.REFERENCES1. World Health Organization - WHO. Health topics:Violence [acesso em 2012 Jan 20]. Disponível em:http://www.who.int/topics/violence/en/2. Silo. Dicionário do novo humanismo. [editordesconhecido]; 1996. (Obras Completas, v. 2).3. World Health Organization - WHO. The World reporton violence and health [acesso em 2012 Jan 22].Disponível em: http://www.who.int/violence_injury_prevention/violence/world_report/en/index.html4. Ministério da Saúde (BR), Secretaria de Vigilância emSaúde. Impacto da violência na saúde dos brasileiros.Brasília: Ministério da Saúde; 2005. (Série B. TextosBásicos de Saúde)5. Minayo MCS. Violência: um problema para a saúde dosbrasileiros. In: Ministério da Saúde (BR), Secretaria deVigilância em Saúde. Impacto da violência na saúdedos brasileiros. Brasília: Ministério da Saúde; 2005.(Série B. Textos Básicos de Saúde). p. 9. Anexo I.6.